2015
DOI: 10.1053/j.seminhematol.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetic Basis of Diffuse Large B-Cell Lymphoma

Abstract: The pathogenesis of DLBCL is strongly linked to perturbation of epigenetic mechanisms. The germinal center (GC) B-cells from which DLBCLs arise are prone to instability in their cytosine methylation patterns. DLBCLs inherit this epigenetic instability and display variable degrees of epigenetic heterogeneity. Greater epigenetic heterogeneity is linked with poor clinical outcome. Somatic mutations of histone modifying proteins have also emerged as a hallmark of DLBCL. The effect of these somatic mutations may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 77 publications
(158 reference statements)
0
34
0
5
Order By: Relevance
“…12 These observations open the pathway to specific DNA methyltransferase and histone methyltransferase inhibitors designed to erase aberrant epigenetic programming. 13 Several studies have investigated the genetic landscape of relapsing DLBCL patients and identified TP53, FOXO1, MLL3, CCND3, NFKBIZ, and STAT6 as top candidate genes for therapeutic resistance. 14 …”
Section: Patients With Early Relapsementioning
confidence: 99%
“…12 These observations open the pathway to specific DNA methyltransferase and histone methyltransferase inhibitors designed to erase aberrant epigenetic programming. 13 Several studies have investigated the genetic landscape of relapsing DLBCL patients and identified TP53, FOXO1, MLL3, CCND3, NFKBIZ, and STAT6 as top candidate genes for therapeutic resistance. 14 …”
Section: Patients With Early Relapsementioning
confidence: 99%
“…However, this instability can also contribute to malignant transformation, and epigenetic changes remain a major feature of DLBCL cells. Genes that function as epigenetic regulators are commonly mutated in DLBCL, with less intratumoral heterogeneity than other cancer‐driving mutations, suggesting a role in early tumorgenesis …”
Section: Introductionmentioning
confidence: 99%
“…In B-NHL, genetic and epigenetic alterations create tumor phenotypes that are protected against immune cytolysis. [1][2][3][4][5][6][7] Immune escape also evolves through the concerted upregulation of gene expression. 8 For example, the B-NHL subtypes FL and DLBCL upregulate the expression of genes involved in the PD1/PDL1-2 axis, the CTLA4 ligand axis, the biosynthesis of immunosuppressive Galectin 3, and the genes IDO1, VEGFA, PGE2, IL10, and HGF, among several others.…”
Section: Introductionmentioning
confidence: 99%